INOVASI MEDIA PEMBELAJARAN DIGITAL DENGAN APLIKASI CANVA PADA MATA PELAJARAN GEOGRAFI UNTUK MENINGKATKAN HASIL BELAJAR KELAS X DI SMAN 5 KUPANG - Uba, Inggit Larasati; Pamungkas, Bella Theo Tomi; Sukmawati, Sukmawati (Jurnal Geografi, 2022)
This study aims to (1) determine the development of digital learning media with the Canva application in geography subjects to improve class X learning outcomes at SMA Negeri 5 Kupang. (2) determine the feasibility level of learning media with the Canva application for geography subjects to improve class X learning outcomes at SMA Negeri 5 Kupang. (3) determine the effectiveness of digital learning media innovation with the Canva application in geography subjects to improve class X learning outcomes at SMA Negeri 5 Kupang. Creative and active digital learning media is Canva using the ADDIE Model Research and Development (Analysis, Design, Development, Implementation and Evaluation) method. The feasibility level of media using Canva is seen from the assessment of two validators, namely media experts and material experts. Based on the results of the assessment of the two validators obtained an average score of 86% with a very good or valid category, it means that the learning media using the Canva application is feasible/valid to be used in learning and student responses obtained an average score of 85% with the category is very suitable for use in learning. After that, a trial was carried out on students of SMAN 5 Kupang to see the effectiveness of the learning media using the Canva application, there was an increase in student learning outcomes. The results before using the media (pre test) and after using the media (post test) obtained the difference/comparison value of 64 and 78. Based on the results of the comparison of the two that using the N-Gain formula, the value was 0.38 with a good/enough category. effective, meaning that learning media using the Canva application on the dynamics of the planet earth as a living space can effectively improve student learning outcomes.